2013
DOI: 10.1016/j.cell.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The Fractalkine/CX3CR1 System Regulates β Cell Function and Insulin Secretion

Abstract: Summary Here, we demonstrate that the fractalkine(FKN)/CX3CR1 system represents a previously undescribed regulatory mechanism for pancreatic islet beta cell function and insulin secretion. CX3CR1 KO mice exhibited a marked defect in glucose and GLP1-stimulated insulin secretion, and this defect was also observed in vitro in isolated islets from CX3CR1 KO mice. In vivo administration of FKN improved glucose tolerance with an increase in insulin secretion. In vitro treatment of islets with FKN increased intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
127
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(143 citation statements)
references
References 44 publications
11
127
3
2
Order By: Relevance
“…Our results on diet-induced obesity in Cx3CR1 gfp mice differ from other reports on this model. For instance, Morris et al [26] and Lee et al [27] failed to detect differences in HFD induced body weight and adiposity in fractalkine receptor KO mice and controls. These discrepancies might be due to different fat composition (60% fat for Morris vs.…”
Section: Discussionmentioning
confidence: 99%
“…Our results on diet-induced obesity in Cx3CR1 gfp mice differ from other reports on this model. For instance, Morris et al [26] and Lee et al [27] failed to detect differences in HFD induced body weight and adiposity in fractalkine receptor KO mice and controls. These discrepancies might be due to different fat composition (60% fat for Morris vs.…”
Section: Discussionmentioning
confidence: 99%
“…Other data have provided evidence that treatment of islets with CX3CL1 increased intracellular Ca 2+ and potentiated insulin secretion in both mouse and human islets. Moreover, expression of CX3CL1 in islets of mice was decreased by ageing and high-fat diet feeding/obesity [59]. Further studies are needed to understand how fractalkine affects pancreatic function.…”
Section: Myokines and Metabolic Regulationmentioning
confidence: 99%
“…Recently, there has been renewed interest in the CX3CR1 gene with the discovery of its role in the pancreatic β-cell insulin secretory pathway (8). With their comprehensive studies using CX3CR1 KO mice islets, Lee et al (8) observed that attenuation of FKN/CX3CR1 system underlie beta cell dysfunction and insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…With their comprehensive studies using CX3CR1 KO mice islets, Lee et al (8) observed that attenuation of FKN/CX3CR1 system underlie beta cell dysfunction and insulin secretion. The 280M and 249I variants alter ligand-receptor binding affinity and are believed to influence an increased susceptibility to T2DM in the carrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation